Chromium sulfide halide monolayers: intrinsic ferromagnetic semiconductors with large spin polarization and high carrier mobility. Issue 37 (19th September 2018) - Guo, Yilv; Zhang, Yehui; Yuan, Shijun; Wang, Bing; Wang, Jinlan
Abstract : We have demonstrated three intrinsic ferromagnetic semiconductor-chromium sulfide halide monolayers with large spin polarization and high carrier mobilities. Abstract : Two-dimensional (2D) ferromagnetic semiconductors (FMSs) are desirable for their potential to enhance the functionality of semiconductor devices via the utilization of spin degrees of freedom. Herein, we predict a series of intrinsic FMS monolayers in the chromium sulfide halide CrSX (X = Cl, Br, I) family with large spin polarization, large magnetic moments and high Curie temperatures. Such CrSCl and CrSBr monolayers also have high hole mobilities up to 6.6 × 10 3 and 5.3 × 10 3 cm 2 V −1 s −1, respectively. Furthermore, these 2D monolayers exhibit excellent dynamic and thermal stabilities and a small exfoliation energy from the bulk. These intrinsic FMSs with their high mobilities may provide competitive candidates for next-generation spintronics and electronics.